Comparison of the Effectiveness of Blended Project-Based Learning and Project-Based Learning Strategies on Chemistry Concept Understanding - Willy agustina Bangun; Alfiati Hasanah; Ririn Ningkeula (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2026)
Given technological advancements, innovation is required to better tailor project-based learning to students who are predominantly "digital natives." Consequently, combining project-based learning with technology offers an ideal solution, particularly within the context of higher education. Blended project-based learning enables students to access materials, engage in discussions, and complete coursework and projects—whether face-to-face or virtually and through both synchronous and asynchronous modes. The application of blended project-based learning allows for the integration of technology, thereby enriching the teaching and learning process and motivating learners to participate actively. The hypothesis proposed is that there is a significant difference in conceptual understanding between the group using the blended project-based learning strategy and the group using the project-based learning strategy. The findings of this study indicate a difference in students' conceptual understanding between those taught using the blended project-based learning strategy and those taught using project-based learning. It is advisable to possess technological proficiency, a strong willingness to learn, and a sense of curiosity. These qualities are crucial for the success of the blended learning process, given that blended learning is an instructional strategy that operates across various contexts and timeframes